Brand origin effects during economic declines - Vieira, Vitor Azzari (2022)
This study examines the preference for brands perceived as domestic and as foreign during economic declines. This research is classified as a quantitative multimethod divided into two main studies. In the first study, we developed an econometric model to analyze brand market share based on economic downturns, brand-origin perception, and their interaction. The model is tested on four years of longitudinal data from consumer-packaged-goods (CPG) brands combined with a self-administrated questionnaire with consumers to infer their perception about the origin of each brand. In the second study, we conducted a survey in a developed and an emerging market to analyze the effect of consumer risk aversion as the underlying mechanism of this phenomenon and consumer xenocentrism as a boundary condition. The findings demonstrate that the preference for brands that consumers most identified as domestic suffered more damage during economic contractions than brands they perceived as foreign. Further analyzes show that the relationship between economic downturns and the preference for brands based on their perceived origin is mediated by consumer risk aversion. In addition, consumer xenocentrism moderates the mediating effect of risk aversion. The main contribution of this paper is generating a better understanding of brands’ resistance to economic contractions based on their perceived country of origin. Moreover, we provide strategic recommendations to brands based on their brand-origin perception and the country’s economic situation.